2015
DOI: 10.1587/transcom.e98.b.854
|View full text |Cite
|
Sign up to set email alerts
|

Interference-Aware Channel Segregation Based Dynamic Channel Assignment for Wireless Networks

Abstract: Recently, we proposed an interference-aware channel segregation based dynamic channel assignment (IACS-DCA). In IACS-DCA, each base station (BS) measures the instantaneous co-channel interference (CCI) power on each available channel, computes the moving average CCI power using past CCI measurement results, and selects the channel having the lowest moving average CCI power. In this way, the CCI-minimized channel reuse pattern can be formed. In this paper, we introduce the autocorrelation function of channel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Furthermore, the superiority of the proposed algorithm compared to a fixed channel allocation (FCA) mechanism is proven. Based on this mechanism, the authors in [11] examine several metrics such as the autocorrelation function, the fairness index of channel reuse pattern and the minimum co-channel distance among the BSs. From their analysis, it can be seen that the proposed scheme forms a CCI minimized channel reuse pattern that ameliorates the signal-tointerference ratio (SIR) compared to other channel assignments schemes.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the superiority of the proposed algorithm compared to a fixed channel allocation (FCA) mechanism is proven. Based on this mechanism, the authors in [11] examine several metrics such as the autocorrelation function, the fairness index of channel reuse pattern and the minimum co-channel distance among the BSs. From their analysis, it can be seen that the proposed scheme forms a CCI minimized channel reuse pattern that ameliorates the signal-tointerference ratio (SIR) compared to other channel assignments schemes.…”
Section: Related Workmentioning
confidence: 99%
“…Using this technique, an efficient stable channel re-use pattern is formed and the system performance is ameliorated. Due to the inherent advantages of this method, various DCA mechanisms based on channel segregation have been proposed by the research community [9][10][11][12]. However, the majority of the DCA schemes in the literature consider that the SBSs do not differentiate between traffic requests from user equipment (UE) applications, even if the applications do not have the same priority from the user point of view.…”
Section: Introductionmentioning
confidence: 99%
“…The centralized DCA may not be practical due to its prohibitively high computational complexity and back haul communication. Recently, we proposed an interference-aware channel segregation based DCA (IACS-DCA) [1,2,3], which is categorized into distributed DCA. IACS-DCA can form a channel reuse pattern with low CCI in a distributed manner [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we proposed an interference-aware channel segregation based DCA (IACS-DCA) [1,2,3], which is categorized into distributed DCA. IACS-DCA can form a channel reuse pattern with low CCI in a distributed manner [1,2,3]. We have shown that IACS-DCA can solve CCI problem in HetNet in a distributed manner [3].…”
Section: Introductionmentioning
confidence: 99%
“…Since the CCI limits the network capacity, it is necessary to spatially reuse the channels so as to minimize the CCI in a network. Recently, we proposed IACS-DCA [1,2]. It has been shown by numerical computation that IACS-DCA forms a stable channel reuse pattern with low CCI.…”
mentioning
confidence: 99%